Mercy Falls - Krueger, William Kent. (New York : Atria Books, 2005)
Back in the saddle as sheriff of Tamarack County, Cork O$1 (BConnor is lured to the nearby Ojibwe reservation on what appears to be a routine call$1 (Bonly to become the target of sniper fire. Soon after, he$1 (Bs called to investigate a mutilated body found perched above the raging waters of Mercy Falls. The victim is Eddie Jacoby, a Chicago businessman negotiating an unpopular contract between his management firm and the local Indian casino. Sparks fly when the wealthy Jacoby family hires a beautiful private investigator to consult on the case. But once Cork discovers an old and passionate tie between one of the Jacoby$1 (Bs sons and his own wife, Jo, he begins to suspect that dark, personal motives lurk behind recent events. Murder, greed, sex, and jealousy hide around every corner in this maze of danger. But somewhere beneath the turbulent Mercy Falls lies the truth$1 (Band Cork is determined to find it.s
Keywords: O'Connor, Cork -- (Fictitious character) -- Fiction; Private investigators -- Illinois -- Chicago -- Fiction; Rich people -- Crimes against -- Fiction; Businessmen -- Crimes against -- Fiction; Chicago (Ill.) -- Fiction; Mystery fiction